Analisis Keputusan Pembelian dan Loyalitas Konsumen Berdasarkan Faktor Promosi Online, Physical Evidence, dan Store Atmosphere (Studi Kasus Produk Franchise Kutaradja Fried Chicken Cabang Bireuen) - Cut Bulan Amanda; Kamaruddin Kamaruddin; Fatimah Zuhra (Singkite Journal, 2026)
This study aims to analyze purchasing decisions and consumer loyalty by investigating the impact of online promotions, physical evidence, and store atmosphere. It is a survey-based study focusing on the Kutaradja Fried Chicken franchise (Bireuen branch). A quantitative approach was employed, utilizing a sample of 90 respondents selected through purposive sampling. Data were collected via Likert-scale questionnaires and analyzed using multiple linear regression. The results indicate that: (1) Individually, online promotions, physical evidence, and store atmosphere have a positive and significant effect on purchasing decisions. (2) Regarding consumer loyalty, neither online promotions nor physical evidence showed a significant impact; conversely, store atmosphere had a positive and significant effect on consumer loyalty (significance value of 0.000). (3) Simultaneously, the three aspects (online promotions, physical evidence, and store atmosphere) contributed positively, explaining 80.9% of the variation in consumer purchasing decisions and 69.8% of the variation in consumer loyalty. Consequently, these findings serve as a basis for the Kutaradja Fried Chicken franchise to enhance purchasing decisions, with store atmosphere emerging as a particularly crucial factor in fostering consumer loyalty.